Disparities in sleep-disordered breathing: epidemiology, mechanisms, and pathways toward equity– a narrative review - Adrianna Elashker; Justin A. Fiala (Current Opinion in Pulmonary Medicine, 2026)
Purpose of review Sleep-disordered breathing (SDB), encompassing obstructive sleep apnea (OSA) and related conditions, affects tens of millions of individuals in the United States and is associated with substantial cardiovascular, metabolic, and neurocognitive morbidity. However, the burden of SDB is not equally distributed across racial, ethnic, and socioeconomic groups, with significant disparities in referral, diagnosis, and treatment of these conditions within traditionally underserved populations. Recent findings Racial and ethnic minority populations, most notably Black, Hispanic/Latinx, and Asian Americans, experience higher prevalence of SDB, greater severity at diagnosis, and lower rates of effective treatment compared with non-Hispanic White populations. Societal determinants including neighborhood disadvantage, occupational exposures, structural racism, and variable/suboptimal access to diagnosis and treatment propagate these inequities resulting in disparities in treatment outcomes, as exemplified by lower adherence rates to continuous positive airway pressure (CPAP) therapy in minoritized groups, even after adjustment for clinical confounders. Summary Addressing disparities in SDB requires multilevel interventions spanning individual clinical care, health system redesign, and policy reform. Culturally adapted diagnostic pathways, community-engaged implementation strategies, and expanded insurance coverage for sleep studies and positive airway pressure therapy represent actionable near-term priorities.